2003
DOI: 10.1128/aac.47.6.1853-1861.2003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Cefepime in Patients with Various Degrees of Renal Function

Abstract: This study evaluated the pharmacokinetics of cefepime in 36 patients with different levels of renal function. Pharmacokinetic and pharmacodynamic parameters were calculated using samples obtained at steady state. Patients with creatinine clearance (CL CR ) of >100 ml/min had more rapid clearance (CL) and a lower minimum concentration in serum (C min ). C min in this group was found to be 3.3 ؎ 3.6 mg/liter (mean and standard deviation), compared to 19.5 ؎ 21.5 mg/liter in patients with a CL CR of between 60 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 17 publications
4
83
0
2
Order By: Relevance
“…Its V is slightly lower than that of total body water, and it exhibits low protein binding of 21% (15). It is almost exclusively eliminated in the urine, with a total CL approximating that of glomerulofiltration (26). Studies of children and older infants have indicated more-rapid elimination than with adults, requiring larger mg/ kg doses or more frequent administration or both for pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Its V is slightly lower than that of total body water, and it exhibits low protein binding of 21% (15). It is almost exclusively eliminated in the urine, with a total CL approximating that of glomerulofiltration (26). Studies of children and older infants have indicated more-rapid elimination than with adults, requiring larger mg/ kg doses or more frequent administration or both for pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Target pharmacodynamic exposures are traditionally derived from in vitro and in vivo animal infections models, with limited human data to validate these findings. Human studies with cephalosporins have produced variable % ƒT Ͼ MIC exposure data for microbiological success (12,13,37). Others have suggested enhanced ␤-lactam activity by maintaining a ƒC min / MIC Ͼ 4 to 6 (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Even the NCCLS frequently relies on healthy-subject data to assess the viability of MIC breakpoints. When possible, PK data should be derived from the population of interest (1,12,22,30,32,33). In summary, 3.375 g of piperacillin-tazobactam given intravenously every 6 h performed well, achieving excellent target attainment rates for MICs of Յ8 (piperacillin) and 4 (tazobactam) mg/liter.…”
Section: Discussionmentioning
confidence: 99%
“…Monte Carlo simulation has been integrated with accepted pharmacodynamic models to compare antimicrobials and determine their abilities to achieve critical dynamic endpoints (1,12,13,15,(20)(21)(22)32). It is a mathematical technique in which parameter values are randomly drawn from a multivariate distribution.…”
Section: Discussionmentioning
confidence: 99%